Digitalization and development cooperation: An assessment of the debate and its implications for policy - Veronika Heimerl; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2018)
Digitalization technologies, such as automation, robotization, artificial intelligence and Big Data are increasingly shaping economic processes. In public discourse, extreme outlooks are widespread. Either digital technologies will provide the solution to most contemporary problems, or dystopian scenarios claim that digital technologies make human labor redundant for production processes, resulting in soaring unemployment rates and widespread social disintegration. Against this backdrop, research on the impacts of digitalization on developing countries is still at an early stage. This briefing paper provides a critical summary of the literature on the challenges and potentials of digitalization for developing economies. A sober account of the historical evidence suggests that both euphoria and dystopian views are misplaced. The major policy challenge for development cooperation will consist in supporting LDC governments in their efforts to manage the effects of the economic and social transition process brought about by digitalization.
Keywords: 330; digitalization; automation; robotization; technological revolution; development cooperation; developing countries